Prospective of forest sector’s organizational system in Chihuahua, Mexico - Vázquez-Álvarez, Susana; Luján-Álvarez, Concepción; Olivas-García, Jesús Miguel; González-Hernández, Hilda Guadalupe; Luján-Álvarez, Humberto (Instituto de Ecología, A.C., 2017)
The forestry organization system in Chihuahua, Mexico was studied for establishing an integral strategy to promote its development. The methodology included three stages: situational diagnosis of the system; prospective structural analysis, and the approach of the integration strategy. For the diagnosis, the actors were grouped into six subsystems: a complete census was carried out, interviewing each one of the actors, and the characterization of the key strategic variables of the organization system was obtained, identifying strengths, opportunities, weaknesses and threats, and the desirable future of the system. In the prospective structural analysis, the level of direct influence and dependence among the variables was determined by applying the Matrix of Cross Impacts - Multiplication Applied to Matrix (MicMac) software. In addition, the integration strategy was generated based on the results of the structural analysis considering the strategic variables and the vision to 2022. As a result, the diagnosis identified little coordination and linkage among system actors, and insufficient leadership. The structural analysis identified the variables with greater motricity and dependence to improve the development of the system: organizational structure, interinstitutional coordination mechanisms and vertical and horizontal integration. Finally, an integral strategy was established that contains the most strategic and most dependent strategic variables, the desirable future and the strategies to achieve that future. It is concluded that the forest organization system has little coordination and linkage among actors and limited association culture, for that, it was necessary to establish the integration strategy in order to get a better response to the demands of national and international competitiveness.